2019
DOI: 10.1002/ijc.32307
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas in patients over 90: Natural history and treatment—A nationwide study over 6 years

Abstract: Soft tissue sarcomas (STS) are rare tumors accounting for less than 1% of human cancers. While the highest incidence of sarcomas is observed in elderly, this population is often excluded or poorly represented in clinical trials. The present study reports on clinicopathological presentation, and outcome of sarcoma patients over 90 recorded in the http://netsarc.org French national database. NETSARC (http://netsarc.org) is a network of 26 reference sarcoma centers with specialized multidisciplinary tumor board (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…When considering cutaneous AS, 10 5-year OS was even higher, superior to 90% for patients with dermatofibrosarcoma protuberans, leiomyosarcoma or malignant fibrous histiocytoma. As previously expected, 3 , 6 8 visceral AS, distant metastases at diagnosis and age ⩾ to 70 years were predictive of worse OS in our cohort ( Figure 1 ). In contrast, a French retrospective multicenter study (June 1980 to October 2009) of 107 patients with localized AS revealed higher 1-year and 5-year OS rates at 74.8% (95% CI: 70.7–78.9) and 39.8% (95% CI: 30.6–43.2), respectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…When considering cutaneous AS, 10 5-year OS was even higher, superior to 90% for patients with dermatofibrosarcoma protuberans, leiomyosarcoma or malignant fibrous histiocytoma. As previously expected, 3 , 6 8 visceral AS, distant metastases at diagnosis and age ⩾ to 70 years were predictive of worse OS in our cohort ( Figure 1 ). In contrast, a French retrospective multicenter study (June 1980 to October 2009) of 107 patients with localized AS revealed higher 1-year and 5-year OS rates at 74.8% (95% CI: 70.7–78.9) and 39.8% (95% CI: 30.6–43.2), respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Factors including age ⩾ to 70 years, male gender, unmarried status, pre-existing lymphedema, primary site of AS (cutaneous versus visceral), tumor size ⩾5 cm, tumor depth, distant metastases at diagnosis and non-surgery were reported to be independently associated with poor survival on prognosis. 3,7,8 In a previous prospective French study 9 including 658 patients with soft tissue sarcomas, 28 AS were identified. Among them, radiation-induced AS represented 18% out of all cases and only one case of Stewart-Treves syndrome was identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiosarcomas are very rare, accounting for approximately 1% to 2% of soft tissue sarcomas, [ 35 ] which represent only 1% to 2% of all tumors. [ 36 ] We included all cases that were identified at our hospital. In addition, the possibility of differential diagnoses in angiosarcoma patients could not be ruled out; thus, some cases were not identified in this database.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In 2010, approximately 40% of patients with limb STS were diagnosed in those aged over 65 years, 1 but historically the elderly age group are under-represented in clinical trials. [4][5][6] Better strategies for the management of long-term conditions mean that the population is progressively ageing, and the NHS is seeing an increasing number of patients presenting with symptoms and signs of STS in the very elderly age range (over 90 years cohort). 1 The management, local recurrence, and overall survival rates in the middle-aged and elderly population are well documented, 3,7 but insufficient evidence exists to guide treatment in the very elderly age group.…”
Section: Introductionmentioning
confidence: 99%